Pelatihan Dan Pendampingan Digital Marketing pada UMKM Industri Olahan Hasil Laut di Kelurahan Sukolilo Baru, Kenjeran Surabaya - Margaretha Ardhanari; Gratianus Edwi Nugrohadi; Monica Ajeng Erwita (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Crackers made out of Seafood are a typical product produced by SMEs in the Kenjeran area of Surabaya. This product is a product that is always sought after by local residents and tourists, when visiting Surabaya, as well as tourist destinations in the Kenjeran area. But since the pandemic, the sales of these SMEs have decreased, due to the social restrictions imposed by the government. In order to reactivate the opportunities and capabilities of the SMEs in the marine product processing industry after the COVID-19 pandemic, a new breakthrough is needed regarding marketing efforts that can increase sales. It is because of this SMEs still use the conventional method, which is just waiting for costumers to come and buy, while the products sold have a limited shelf life. Based on the problems faced by this SMEs, the community service team designed training and assistance using a service learning strategy that aims to: (a) Provide an understanding of the need to change the perspective on using technology to market products; (b) Introducing various social media and market places that can be used to market products; (c) Provide orientation on free promotional media to the creation of product accounts on promotional media; (d) Making product photos with cellphone cameras for media content; (e) Writing and uploading short content on photo images on social media. The result of community service is the ability and skills of the small-medium enterprises in marketing products digitally, namely through social media and market places